Efficacy of traditional Chinese exercises in improving anthropometric and biochemical indicators in overweight and obese subjects: A systematic review and meta-analysis. Issue 12 (24th March 2023) - Yang, Qianfang; Wang, Fan; Pan, Limin; Ye, Ting
Abstract : Background: The efficacy of traditional Chinese exercise (TCE)-based intervention in the improvement of anthropometric and biochemical indicators in overweight and obese patients is controversial. In this regard, the aim of this review was to summarize the evidence of TCE interventions to evaluate their effectiveness on the anthropometric and biochemical indicators of overweight and obese patients. Method: Five databases were systematically searched for relevant articles published from inception to October 2022. Randomized controlled trials examining TCE intervention in overweight and obese patients The treatment effects were estimated using a random-effect meta-analysis model with standardized mean differences (Hedges' g ). The categorical and continuous variables were used to conduct moderator analyses. This review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (identifier CRD42022377632). Result: Nine studies involving a total of 1297 participants were included in the final analysis. In the anthropometric indicators outcomes, the meta-analytic findings revealed large and significant improvements in body mass index ( g = 1.44, 95% confidence interval [CI] = 1.27–1.61, P = .000, I 2 = 99%), weight ( g = 1.47, 95% CI = 1.25–1.68, P = .000, I 2 = 95%), fat percentage ( g = 1.22, 95% CI = 0.52–1.93, P = .000, I 2 = 93%), and small and significant improvements in waist circumference ( g = 0.38, 95% CI = 0.21–0.54, P = .000, I 2 = 99%). In the biochemical indicators outcomes, the findings revealed large and significant improvements in low density lipoprotein ( g = 2.08, 95% CI = 1.80–2.37, P = .000, I 2 = 98%), moderate and significant improvements in triglyceride ( g = 0.69, 95% CI = 0.56–0.81, P = .000, I 2 = 96%), small and significant improvements in total cholesterol ( g = 0.37, 95% CI = 0.19–0.54, P = .000, I 2 = 77%), and high-density lipoprotein ( g = −0.71, 95% CI = −0.86 to 0.57, P = .000, I 2 = 99%). The moderator shows that the effects of TCE on anthropometric and biochemical indicators were moderated by frequency of exercise, exercise duration, and type of control group. Conclusion: TCE intervention is a beneficial non-pharmacological approach to improving anthropometric and biochemical indicators in overweight and obese subjects, especially in body mass index, weight, fat percentage, triglyceride, and low-density lipoprotein. The clinical relevance of our findings is pending more extensive trials and more rigorous study designs to strengthen the evidence.